2018
DOI: 10.29261/pakvetj/2018.078
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mixed Infection of Avian Influenza and Newcastle Disease Viruses in Chickens in Indonesia by Immunopathologic Immunohistochemistry Double Staining

Abstract: Avian influenza virus (AIV) and Newcastle disease virus (NDV) are systemic disease that is highly infectious with high morbidity and mortality rates, and highly detrimental to economic value in the domestic and commercial poultry industries. Generally, in the field there is a mixed infection of AIV and NDV, each of which is highly pathogenic. Clinical signs are difficult to distinguish, so immunopathological immunohistochemistry (IHC) double staining was developed with the ability to confirm the diagnosis of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
2
0
2
Order By: Relevance
“…In the present study, the lungs appeared swollen and opaque and had severe, diffuse, spotted and linear congestion, and hemorrhages. It was reported that AIV infections in chickens are characterized by lesions in the lungs as observed in the present study [23,25]. Chickens infected with AIV also show significant hemorrhagic lesions [29].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the present study, the lungs appeared swollen and opaque and had severe, diffuse, spotted and linear congestion, and hemorrhages. It was reported that AIV infections in chickens are characterized by lesions in the lungs as observed in the present study [23,25]. Chickens infected with AIV also show significant hemorrhagic lesions [29].…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, we describe an immunopathological approach based on immunohistochemistry to detect AIV infections. We suggest that this biotechnological method fulfills the aforementioned criteria and should be applied to control and reduced zoonotic risks, such as bird flu pandemics in Indonesia [21-25].…”
Section: Introductionmentioning
confidence: 99%
“…Oleh karena itu, penurunan kejadian AI pada manusia perlu difokuskan pada pencegahan dan kontrol infeksi unggas serta perlunya strategi pengendalian pada unggas untuk mencegah penyebaran virus dan menyebabkan wabah terutama di negara-negara berkembang (Dharmayanti et al, 2005;Chon et al, 2008;Zeynalova et al, 2015 potong setara dengan 10 copy/µl (Payungporn et al, 2006 (Capua et al, 2003;Tarigan, 2015 (Kumar et al, 2003). P e n e g u h a n d i a g n o s i s i n f e k s i VA I berdasarkan gejala klinis pada unggas yang mengalami penurunan produksi seringkali terjadi proporsi diagnosis positif dan negatif palsu, karena memiliki kemiripan dengan penyakit unggas yang lainnya, seperti Newcastle disease (ND) (Wasito et al, 2018). (Wasito et al, 2014;Wasito et al, 2018).…”
Section: Pendahuluanunclassified
“…P e n e g u h a n d i a g n o s i s i n f e k s i VA I berdasarkan gejala klinis pada unggas yang mengalami penurunan produksi seringkali terjadi proporsi diagnosis positif dan negatif palsu, karena memiliki kemiripan dengan penyakit unggas yang lainnya, seperti Newcastle disease (ND) (Wasito et al, 2018). (Wasito et al, 2014;Wasito et al, 2018). Namun, untuk wilayah atau laboratorium yang mempunyai keterbatasan sarana infrastruktural modern, pemeriksaan lesi patologis anatomis dan histopatologis tersebut akan sangat membantu peneguhan diagnosa VAI, karena uji tersebut relatif cepat dan biaya terjangkau (Webster & Hulse, 2004).…”
Section: Pendahuluanunclassified
“…Sometimes the clinical signs of avian influenza may be difficult to differentiate from other endemic diseases of poultry (Swayne, 2007;Wasito et al, 2018). Numerous studies show that the occurrence of new cases increased as compare to the past.…”
Section: Introductionmentioning
confidence: 99%